The Implementation of Data Mining in Grouping Community Satisfaction Index in The Regional Office of The Ministry of Law and Human Rights of Bengkulu Province - Melvayanti Lubis (Jurnal Komputer, Informasi dan Teknologi, 2021)
Data mining application for grouping community satisfaction is made using the Visual Basic .Net programming language. To classify community satisfaction, the application has applied the Decision Tree Method by looking at the results of the Gain and Entropy values ​​in each branch. The branch consists of 7, namely service procedures, service information, completion time, officer competence, technological facilities, complaint handling, and integrity. With this application, it is hoped that it can help the Ministry of Law and Human Rights of Bengkulu Province in analyzing and knowing community satisfaction with the services provided. Based on the results of the tests, the functionality of the data mining application is for classifying community satisfaction well as it should, and is able to provide information on the results of community satisfaction analysis through the decision tree approach